Water calorimetry in MR‐linac: Direct measurement of absorbed dose and determination of chamber kQmag. Issue 12 (24th October 2020) - D'Souza, Mark; Nusrat, Humza; Iakovenko, Viktor; Keller, Brian; Sahgal, Arjun; Renaud, James; Sarfehnia, Arman
Abstract : Purpose: To use a portable 4°C cooled MR‐compatible water calorimeter to measure absorbed dose in a magnetic resonance‐guided radiation therapy (MRgRT) system. Furthermore, to use the calorimetric dose results and direct cross‐calibration to experimentally measure the combined beam quality and magnetic field correction factor ( k Q mag ) of a clinically used reference‐class ionization chamber placed under the same radiation field. Methods: An Elekta Unity MR‐linac (7 MV FFF, B  = 1.5 T) was used in this study. Measurements were taken using the in‐house designed and built water calorimeter. Following preparation and cooling of the system, the MR‐compatible calorimeter was positioned using a combination of MR and EPID imaging and the dose to water was measured by monitoring the radiation‐induced temperature change. Immediately after the calorimetric measurements, an A1SL ionization chamber was placed inside the calorimeter for direct cross‐calibration. The results allowed for a direct and absolute experimental measurement of k Q mag for this chamber and comparison against existing Monte Carlo values. Results: The calorimeter was successfully positioned using imaging in under an hour. The 1‐hour setup time is from the time the calorimeter leaves storage to the first calorimetric measurement. Absorbed dose was successfully measured with a relative combined standard uncertainty of 0.71 % ( k =  1). Through a cross‐calibration, the k Q mag for an Exradin A1SL ionization chamber, set up perpendicular to the incident photon beam and opposite to the direction of the Lorentz force, was directly determined in water in absolute terms to be 0.977 ± 0.010. The currently published k Q mag results, obtained via Monte Carlo calculations, agree with experimental measurements in this work within combined uncertainties. Conclusions: A novel design of an MR‐compatible water calorimeter was successfully used to measure absorbed dose in an MR‐linac and determine an experimental value of k Q mag for a clinically used ionization chamber.